Are vocal characteristics related to leadership patterns in mixed‐species bird flocks?. (23rd May 2018) - Pagani‐Núñez, Emilio; Xia, Xue; Beauchamp, Guy; He, Ruchuan; Husson, John H. D.; Liang, Dan; Goodale, Eben
Abstract : What structures the organization of mixed‐species bird flocks, so that some 'nuclear' species lead the flocks, and others follow? Previous research has shown that species actively listen to each other, and that leaders are gregarious; such gregarious species tend to make contact calls and hence may be vocally conspicuous. Here we investigated whether vocal characteristics are associated with leadership, using a global dataset of mixed‐species flock studies and recordings from sound archives. We first asked whether leaders are different from following or occasional species in flocks in the proportion of the recordings that contain calls (n = 58 flock studies, 145 species), and especially alarm calls (n = 111 species). We found that leaders tended to have a higher proportion of their vocalizations that were classified as calls than occasional species, and both leaders and following species had a significantly higher proportion of their calls rated as alarms compared to occasional species. Next, we investigated the acoustic characteristics of flock participants' calls, hypothesizing that leaders would make more calls, and have less silence on the recordings. We also hypothesized that leaders' calls would be simple acoustically, as contact calls tend to be, and thus similar to each other, as well as being detectable, in being low frequency and with high frequence bandwidth. The analysis (n = 45 species, 169 recordings) found that only one of these predictions was supported: leading species were less often silent than following or occasional species. Unexpectedly, leaders' calls were less similar to each other than occasional species. The greater amount of information available and the greater variety of that information support the hypothesis that leadership in flocks is related to vocal communication. We highlight the use of sound archives to ask questions about behavioral and community ecology, while acknowledging some limitations of such studies.